The "Spalakh" astronomical television system - Kleshchonok, V.V. (Кинематика и физика небесных тел, 2005)
The description of the new astronomical television system “Spalakh” is cited. The system is intended for fast phenomena observations with exact link to time scale. The results of laboratory and actual tests of the system are given.